Invertebrates - Brusca, Richard C.
"For each of 32 currently recognized phyla, Invertebrates, Third Edition presents detailed classifications, taxonomic synopses, updated information on general biology and anatomy, and current phylogenetic hypotheses. Chapters are organized around the "new animal phylogeny," along with basic background on invertebrates. Illustrated with abundant line drawings, color photos, boxes, and tables"--